PENGARUH MEDIA SOSIAL TERHADAP KENAKALAN REMAJA PADA SISWA MAN DI YOGYAKARTA: Cyberbullying, Media Sosial, Siswa - Aidah, Nur; Sukamto, Bambang; Karyono, Karyono; Perdana, Nino Agung; Rahman, Nur; Suparman, Omang (Jurnal De Jure Muhammadiyah Cirebon, 2023)
The influence of social media on juvenile delinquency among students. Social media use has increased rapidly among teenagers, and this study aims to understand its impact on juvenile delinquent behavior. The research method used involves surveys and data analysis from a number of students who actively use social media. The results of this study highlight the need for a more thoughtful approach to youth use of social media. Schools, families and communities need to play a role in providing education about the healthy and safe use of social media. With a better understanding of the influence of social media, we can develop more effective strategies to reduce juvenile delinquency and protect young people from the negative impacts that may arise from uncontrolled social media use. Apart from that, social media can also influence the increase in bullying and cyberbullying behavior among teenagers